Предмет: Математика,
автор: Илья0Левченко
Помогите пожалуйста
Ответы
Автор ответа:
0
4^(x^2 - x) = 8^(3 - x)
Так как, имеем
4 = 2^2
8 = 2^3
2^2(x^2 - x) = 2^3(3 - x)
2x^2 - 2x = 9 - 3x
2x^2 - 2x + 3x - 9 = 0
2x^2 + x - 9 = 0
D = 1 + 8*9 = 73
x1 = ( - 1 + √73)/4
x2 = ( - 1 - √73)/4
Так как, имеем
4 = 2^2
8 = 2^3
2^2(x^2 - x) = 2^3(3 - x)
2x^2 - 2x = 9 - 3x
2x^2 - 2x + 3x - 9 = 0
2x^2 + x - 9 = 0
D = 1 + 8*9 = 73
x1 = ( - 1 + √73)/4
x2 = ( - 1 - √73)/4
Похожие вопросы
Предмет: Геометрия,
автор: tvoyafanatka7
Предмет: География,
автор: morpho999
Предмет: Литература,
автор: ivvo100627
Предмет: Литература,
автор: maxDBlackey
Предмет: Математика,
автор: snezok2010